Frequency and predictors of access site complications of the transfemoral diagnostic coronary procedures - Karakuş, Alper; Arı, Selma; Acar, Temel; Ari, Hasan; Çamcı, Sencer; Tutuncu, Ahmet; Özmen, Gökhan; Melek, Mehmet; Demir, Mehmet (The European Research Journal, 2020)
Objectives: Access site complications (ASC) remain important and common adverse events after coronary angiography. The aim of this study was to evaluate the frequency and predictors of ASC in patients undergoing diagnostic coronary angiography (DCA) via the femoral artery. Methods: In this prospective analytical cross sectional study, DCA was performed in 3972 patients by transfemoral approach. The femoral access site hemostasis was obtained by manual compression in all patients. Demographic characteristics of the patients, size of the arterial sheaths, duration of compression time, patients blood pressure, medications, hemoglobin and platelet levels were recorded. All patients were evaluated for ASC (pseudoaneurysm, bleeding, dissection, hematoma). The ASC rate was calculated and ASC predictors were determined by multivariate analysis. Results: The ASC rate was 1.3% (53 of 3972 patients). The complications were more frequent in female (female: 29 of 53 [54.7%] vs male: 24 of 53 [45.3%]; p = 0.007) and chronic renal failure (CRF) patients (103 of 3919 [2.6%] vs 4 of 53 [7.5%]; p = 0.02). Hemoglobin level was lower (13.40 ± 1.73 vs 12.86 ± 1.75; p = 0.02) and manual compression time was longer (9.19 ± 3.28 min vs 14.53 ± 6.47 min; p < 0.001) in the ASC group. Clopidogrel (188 of 3919 [4.8%] vs 7 of 53 [13.2%]; p = 0.005) and low molecular weight heparin (LMWH) using were more frequent (37 of 3919 [0.9%] vs 7 of 53 [13.2%]; p < 0.001) in the ASC group. According to multivariate analysis; female gender; OR: 2.13, 95% CI: 1.14-3.99 (p = 0.017), presence of CRF; OR: 3.15, 95% CI: 1.06-9.29 (p = 0.038), manual compression time; OR: 1.23, 95% CI: 1.17-1.30 (p < 0.001) and LMWH using; OR: 15.68, 95% CI: 6.05-40.61 (p < 0.001) were predictors of ASC. Conclusions: The incidence of femoral ASC rate was 1.3% in patients with DCA. Female gender, presence of CRF, using LMWH and long manual compression time were predictors of ASC.